A transversalidade literária de Manoel de Barros na pedagogia da educação ambiental no Pantanal - Maekawa, Maria Ester Godoy Pereira (2005)
We have seen, since the XXI century, the consumist world in conflict, with separation among the human beings, vanishment and the compromise of the natural possessions of our planet. The rationalism, the specialization, the wild run for technology have become us cold, unable to understand, to love, to be happy and to communion. The environmental education that we propose goes through the way of participating observation, in a phenomenological perspective that follows the bioregionalism and sociopoetry, understanding poem as human sensibilization instrument. We developed a interdiscipline search, during the period of March 2003 to March 2004, in the Maria Silvino Peixoto de Moura State School, in Barão de Melgaço town, in Mato Grosso, with 6th grade of Medium School, surrounding a PRNH (Private Reserve of Natural Heritage) of SESC Pantanal Hotel, with the study of Manoel de Barros poetry. The students had access to several works of the writer (that lived his childhood in Pantanal), as well as films, cassettes, oral exhibition and debates. Inspite of the difficulty degree of several images (languages pictures) and peculiar vocabulary of the author full of neologism, the teachers expressed the feeling of entusiasm during and in the end of the activities. The study showed the high level of involvement and participation of the search characters (students) that represented the Pantanal environment and culture, through poetry, draws, texts, local recipes book, siriri and cururu stories, prays and blessons. The poem of the author showed to be able to approach geographics or emocionals distances, because there were moments of identification from the characters (environment, plays, culture, traditions and Pantanal terms). The educational pratical set water, trees, birds, garbage, and floor things in motion that are part of Manoel de Barros work can, in our point of view, still make possible, help to public politics that allow the critical and creative expression of the whole national territory students.